2022
DOI: 10.3390/insects13060527
|View full text |Cite
|
Sign up to set email alerts
|

Improved Captures of the Invasive Brown Marmorated Stink Bug, Halyomorpha halys, Using a Novel Multimodal Trap

Abstract: Capture strategies for the brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), are challenging. Here we developed and evaluated a multimodal trap which combines visual and olfactory stimuli. Visual stimuli consisted of LEDs emitting UV-A and visible light. Olfactory stimuli were comprised of the synthetic aggregation pheromone and odours from trapped H. halys individuals. Stink bug attraction at different wavelengths was evaluated in laboratory two-choice bioassays, and different prototype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Our parasitoids were inactive during the scotophase, but we did not test how supplementing UV radiation at night could affect their daily activity. While a stimulatory effect of UV radiation appears to explain the increasing activity in some insects (Johansen et al, 2011), our opposing results may result from an arrestment response (i.e., inhibition of dispersal) following a UV-seeking behaviour in our parasitoids, as found in stink bugs resting on UV-emitting traps (Rondoni et al, 2022).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our parasitoids were inactive during the scotophase, but we did not test how supplementing UV radiation at night could affect their daily activity. While a stimulatory effect of UV radiation appears to explain the increasing activity in some insects (Johansen et al, 2011), our opposing results may result from an arrestment response (i.e., inhibition of dispersal) following a UV-seeking behaviour in our parasitoids, as found in stink bugs resting on UV-emitting traps (Rondoni et al, 2022).…”
Section: Discussionmentioning
confidence: 66%
“…and Trissolcus spp. have also been found to be attracted to UV‐A radiation (Endo & Hironaka, 2017), both host and parasitoid could show similar UV wavelength‐dependent behaviours, potentially compromising the benefits of UV manipulation (e.g., UV‐emitting traps; Rondoni et al, 2022) for increasing crop yield. However, observing an attraction to UV radiation in confined, controlled conditions (microhabitat level) does not necessarily translate to observable effects on parasitism rate in larger, more natural settings (macrohabitat level), as Chiel et al (2006) found for aphid and whitefly parasitoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response behaviors and phototactic mechanisms of insects to different light sources are the main objectives of light-trap technology in order to develop pest control technology using new light sources such as LEDs. Wavelength selectivity and high intensity of LEDs enable them to be specifically designed for targeting pests, protecting biodiversity and the environment [ 26 , 35 ]. S. frugiperda showed the highest average phototactic rate to blue light among the five different LED lights.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting group of studies have been reported with stink bugs (Hemiptera: Pentatomidae), such as Halyomorpha halys (Stål) and the green stink bugs Nezara spp. (Cambridge et al, 2017; Endo et al, 2022; Rice et al, 2017; Rondoni et al, 2022). Similar studies with several moth species, such as the cabbage looper Trichoplusia ni (Hübner) (Lepidoptera: Noctuidae), the Indian meal moth (IMM), Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae), and the tomato leaf miner Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), have used traps with lights plus sex pheromone/kairomone baits for mass trapping adults (Henneberry et al, 1967; Pezhman & Saeidi, 2018; Sambaraju & Phillips, 2008).…”
Section: Introductionmentioning
confidence: 99%